Differential Expression of the miR-200 Family MicroRNAs in Epithelial and B Cells and Regulation of Epstein-Barr Virus Reactivation by the miR-200 Family Member miR-429 - Lin, Zhen (American Society for Microbiology (ASM), 2010)
The miR-200 microRNA family is important for maintaining the epithelial phenotype, partially through suppressing ZEB1 and ZEB2. Since ZEB1 inhibits Epstein-Barr virus (EBV) reactivation, we hypothesized that expression of miR-200 family members in epithelial cells may partly account for higher levels of EBV reactivation in this tissue (relative to nonplasma B cells). Here we show that, whereas miR-200 family members are expressed in epithelial cells, their expression is low in latently infected B cells. Furthermore, the miR-200 family member miR-429 shows elevated expression in plasma cell lines and is induced by B-cell-receptor activation in Akata cells. Lastly, expression of miR-429 can break latency.